2021
DOI: 10.3390/math9192356
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on the Efficiency of LED Energy Enterprises in China by Employing the DEA Model

Abstract: As an essential part of strategic emerging industry, the light emitting diode (LED) industry plays an important role in the development of a national economy as well as being a technology that is pivotal to energy saving and environmental protection. Due to the late start of China’s LED energy industry, there are few related studies, especially on the efficiency of China’s LED energy enterprises. The data envelopment analysis (DEA) method is widely used in efficiency measurement for its significant advantages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A systematic study of efficiency theory was conducted by Farrell in 1957 [ 26 ]. Efficiency evaluation is always expressed as the ratio of an objective’s outputs to inputs at a specific time, from the perspective of management and economics, and has been studied and applied in different fields [ 27 , 28 ]. A DEA model is a specific model of data envelopment analysis, which analyzes the technical efficiency and scale efficiency of decision-making units (DMUs).…”
Section: Model and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic study of efficiency theory was conducted by Farrell in 1957 [ 26 ]. Efficiency evaluation is always expressed as the ratio of an objective’s outputs to inputs at a specific time, from the perspective of management and economics, and has been studied and applied in different fields [ 27 , 28 ]. A DEA model is a specific model of data envelopment analysis, which analyzes the technical efficiency and scale efficiency of decision-making units (DMUs).…”
Section: Model and Datamentioning
confidence: 99%
“…The efficiency measurement of Constant Returns to Scale (CRS) and Variable Returns to Scale (VRS) in DEA would be used to evaluate SCC input–output efficiency in China. To measure the construction efficiency of pilots and its influencing factors, the Banker, Charnes, and Cooper (BCC) model, with the assumption of variable returns to scale, was selected to analyze the technical and scale efficiency for the efficiency evaluation system of SCC pilots, as shown in the following equation [ 28 ]: …”
Section: Model and Datamentioning
confidence: 99%
“…Svetlana et al [19] performed an efficiency evaluation of regional environmental management systems in Russia; the results showed that the efficiency of regional environmental management in many Russian regions has great potential for improvement. Wang et al [20] evaluated the efficiency of LED energy enterprises in China using the DEA model. The results revealed that the total technical efficiency of China's LED energy firms has improved, owing to the LED energy enterprises' focus on technology advancement.…”
Section: Data Envelopment Analysis (Dea) Modelmentioning
confidence: 99%